2016
DOI: 10.1177/0741932516683631
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Reported Knowledge and Implementation of Research-Based Classroom and Behavior Management Strategies

Abstract: Teachers’ reported knowledge about and implementation of research-based classroom and behavior management strategies were examined. A total of 160 elementary teachers from two districts in different regions of the same state completed the researcher-developed Survey of Classroom and Behavior Management. On average, teachers reported to be somewhat knowledgeable and to implement somewhat all of the 10 sets of research-based strategies included in the survey. Teachers appeared to be most knowledgeable and more f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 21 publications
2
51
0
Order By: Relevance
“…Despite significant literature to inform implementation of evidence-based classroom management strategies to improve student behavior (Simonsen et al 2008), teachers often lack the knowledge or training to implement effective classroom management strategies reducing problem behavior responses (Moore et al 2017). Because display of off-task or disruptive behavior can impede learning for all students in the classroom, supporting teachers in implementation of effective management methods is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant literature to inform implementation of evidence-based classroom management strategies to improve student behavior (Simonsen et al 2008), teachers often lack the knowledge or training to implement effective classroom management strategies reducing problem behavior responses (Moore et al 2017). Because display of off-task or disruptive behavior can impede learning for all students in the classroom, supporting teachers in implementation of effective management methods is essential.…”
Section: Introductionmentioning
confidence: 99%
“…During the Preimplementation phase and at study conclusion, a classroom management survey was completed by teachers to provide background information on their understanding and use of best practices in classroom management. This survey was adapted from two different measures—the Classroom Ecology Checklist (CEC; Reinke, Herman, & Sprick, 2011) and the Teachers’ Knowledge and Use of Classroom and Behavior Management Strategies (Borthwisck-Duffy, Lane, & Mahdavi, 2002; Moore, Oliver, & Wehby, 2012)—and consisted of 64 items. The first item set pertained to current knowledge of best practices in classroom management strategy had four response options (1 = no knowledge , 2 = limited knowledge , 3 = somewhat knowledgeable , and 4 = very knowledgeable ; Moore et al, 2012), and has demonstrated good internal consistency reliability (α = .91).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, when teachers are surveyed about the classroom management practices they employ, they consistently report using mostly research-informed, proactive practices at high rates (e.g. Borgmeier, Loman, & Hara, 2016; Cooper et al, 2018; Moore et al, 2017). This finding may be due to the nature of self-report, with some studies revealing that practising teachers tend to report inflated levels of knowledge and use of practices (Hartman & Nelson, 1992; Stark, Snow, Eadie, & Goldfeld, 2016).…”
Section: Introductionmentioning
confidence: 99%